2016
DOI: 10.1038/srep38313
|View full text |Cite
|
Sign up to set email alerts
|

Limited HIV-1 Reactivation in Resting CD4+ T cells from Aviremic Patients under Protease Inhibitors

Abstract: A latent viral reservoir that resides in resting CD4+ T cells represents a major barrier for eradication of HIV infection. We test here the impact of HIV protease inhibitor (PI) based combination anti-retroviral therapy (cART) over nonnucleoside reverse transcriptase inhibitor (NNRTI)-based cART on HIV-1 reactivation and integration in resting CD4+ T cells. This is a prospective cohort study of patients with chronic HIV-1 infection treated with conventional cART with an undetectable viremia. We performed a sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In agreement with our results, the number of productively infected monocytes is nearly 10-fold lower than the number of productively infected CD4+ T cells in the blood of Simian Immunodefiency Virus-infected macaques [ 63 ]. In agreement with decreased Akt activation in resting CD4+ T cells from PI-treated patients [ 21 ], we observed low levels of Akt activation in monocytes isolated from PI-treated patients. By using the proviral HIV DNA assay that allows for evaluating in a quantitative manner the amount of intracellular provirus, we observed that cART was efficient for limiting the size of the HIV-1 reservoir in monocytes and resting CD4+ T cells compared to cART-naïve patients ( Figure 6 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In agreement with our results, the number of productively infected monocytes is nearly 10-fold lower than the number of productively infected CD4+ T cells in the blood of Simian Immunodefiency Virus-infected macaques [ 63 ]. In agreement with decreased Akt activation in resting CD4+ T cells from PI-treated patients [ 21 ], we observed low levels of Akt activation in monocytes isolated from PI-treated patients. By using the proviral HIV DNA assay that allows for evaluating in a quantitative manner the amount of intracellular provirus, we observed that cART was efficient for limiting the size of the HIV-1 reservoir in monocytes and resting CD4+ T cells compared to cART-naïve patients ( Figure 6 ).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have also reported the impact of protease inhibitors (PIs) on Akt signaling in several cell types and in clinical trials [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. We observed previously a critical role for Nef in the hyperactivation of T cells through Akt activation and that blocking Akt activation especially by HIV-1 protease inhibitors (PIs) could limit HIV-1 recovery from latently infected T cells [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that PIs but not non-PIs can limit LRA-mediating reactivation of HIV-1 latent reservoirs. The same group demonstrated that PIs block the reactivation of HIV-1 in resting CD4+ T cells isolated from chronically infected aviremic patients [ 192 ]. In addition to HIV-1 disease progression, Akt signaling also regulates the chromatin remodeling through PcG proteins [ 193 ].…”
Section: Pcg-mediated Epigenetic Silencing and Novel Hiv-1 Reactivatimentioning
confidence: 99%
“…Akt inhibitor may induce H2A ubiquitination and may promote epigenetic silencing of HIV-1 promoter. In addition, cART may impact the block-and-lock strategy of HIV-1 cure, since PIs inhibit Akt signaling and suppress HIV-1 reactivation from latency [ 191 , 192 ]. The use of PIs or Akt inhibitors together with LPAs may synergistically induce viral latency and may contribute to functional cure of HIV by preventing viral reactivation from latent reservoirs (Fig.…”
Section: Pcg-mediated Epigenetic Silencing Will Set the Stage For Blomentioning
confidence: 99%
“…Nonetheless, this approach is limited by resistance mutations that have been reported in vitro [ 4 ]. To note that, beside the canonical “shock and kill” strategy that targets solely the virus, eradication of both HIV-infected cells and virus through the use of Akt inhibitors, Bcl-2 antagonists and XIAP inhibitors for instance, is correspondingly regarded as an alternative “shock and kill” therapeutic approach [ 5 , 6 ].…”
mentioning
confidence: 99%